Histopathological diagnostic criteria of barrett esophagus and its association with endoscopy findings - Rustiasari, Ukhti Jamil; Handjari, Diah Rini (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : In the last decades, the incidence of esophageal adenocarcinoma has significantly increased. Barrett Esophagus (BE) is widely known as a precursor lession of esophageal adenocarcinoma, and it could increase the risk of adenocarcinoma to 30-120 times higher than non-BE patient. The controversy about BE definition is still a problem amongst pathologist. BE is defined as the transition of normal esophageal squamous epithellium into metaplastic columnar epithellium that can be seen through endoscopy at the upper region of gastroesophagus transitional area, and confirmed with hystological examination. Objective : To re-evaluate hystopathological presentation of BE and the classification of dysplasia as well as its association with clinical finding in the form of endoscopy results. Methods : Clinical and hystopathological datas of 71 cases of BE was collected and re-evaluated based on British Society of Gastroenterology Guidelines 2005 criteria, as well as re-evaluating the grade of dysplasia based on WHO Classification of tumours of the digestive system 2010. Results : 51 cases of BE were obtained with male:female ratio 33:18 patients. BE cases were predominated by 51-60 years old age group, in which the mean of patients age was 55 years old. The results of dysplasia grade re-evaluation showed 72,55% non-dysplasia BE case, 3,9% was BE indefinite; 23,53% was BE with low grade dysplasia; and 1,97% was BE with hard grade dysplasia. There were 15 cases (21,12%) that were changed in diagnosis, from BE to non-BE cases. Conclusion : The diagnosis of BE could be made if there are compatibility between endoscopy examination and hystopathological examination, in which BE presentations was found, either in category 1, 2 or 3based on British Society of Gastroenterology Guidelines 2005 and endoscopy indicated supicion of BE. Changes in diagnosis of BE cases into non-BE cases could happen not because there are incompatibilities of the results of these examinations. This might happen due to nescience regarding the importance of the results of endoscopy examination and its compatibility with the results of hystopathological examination.